I think you are asking to find the values of x,y, and z that satisfy all of the three below equations:
2x-y+z=4 <--- Equation 1
x+3y-z=11 <--- Equation 2
4x+y-z=14 <--- Equation 3
First add Equation 1 to Equation 2 which gives:
3x +2y = 15 <--- Equation 4
Now add Equation 1 to Equation 3 getting:
6x= 18
x=3
Put x=3 into Equation 4 getting:
3*3 +2y = 15
2y =15 -9 =6
y = 3
Now put x= 3 and y =3 into Equation 1 getting
2*3 -3 +z=4
6-3 +z = 4
3 +z = 4
z = 4-3 = 1
Hope this helps.
2007-01-05 17:26:00
·
answer #1
·
answered by ironduke8159 7
·
0⤊
0⤋
1) 2x - y + z = 4
2) x + 3y - z = 11
3) 4x + y - z = 14
I guess you wnat to solve a system of three equations in three unknowns. There are various ways to do this. One approach follows:
Manipulate the equations to get two equations in two unknowns, and then solve that system.
Add equation 1 to equation 2
1) 2x - y + z = 4
2) x + 3y - z = 11
- - - - - - - - - - - -
4) 3x + 2y = 15
Subtract equation 3 from equation 2
2) x + 3y - z = 11
3) 4x + y - z = 14
- - - - - - - - - - - -
5) -3x + 2y = - 3
Now add equations 4 and 5
4) 3x + 2y = 15
5) -3x + 2y = - 3
- - - - - - - - - - - -
4y = 12
y = 3
Substitute this result into either equation 4 or 5 to find x
5) -3x + 2y = - 3
- 3x + 2(3) = - 3
- 3x + 6 = - 3
- 3x = - 9
x = 3
Substitute for x and y in one of the original equations to get z
1) 2x - y + z = 4
2(3) - 3 + z = 4
6 - 3 + z = 4
3 + z = 4
z = 1
x = 3, y = 3, z = 1
Check
2) x + 3y - z = 11
3 + 3(3) - 1 = 11
3 + 9 - 1 = 11
11 = 11
3) 4x + y - z = 14
4(3) + 3 - 1 = 14
12 + 3 - 1 = 14
14 = 14
2007-01-05 17:26:09
·
answer #2
·
answered by Anonymous
·
1⤊
0⤋
I first rearranged two of the problems and set them equal to each other. I isolated the z variable first.
z = 4 + y - 2x (first problem)
z = 4x + y - 14 (third problem)
I set them equal to each other...
4 + y - 2x = 4x + y - 14 (then simplify... the ys cancel out)
18 = 6x
**x = 3**
Then I plugged the x=3 into 2 of the problems. First I had...
3 + 3y - z = 11
z = 3 + 3y - 11
So I took that and plugged the value of x (3) and that value of z (above) into the first problem.
2 (3) - y + 3 + 3y - 11 = 4 Simplify...
-2 + 2y = 4
2y = 6
**y = 3**
So now that we know that x = 3, and y = 3, we can plug those numbers into any problem to get the value of z. (I plugged them into the first problem.)
6 - 3 + z = 4
3 + z = 4
z =1
Plug all 3 numbers into all of the equations to see if it works, and it does.
2007-01-05 17:35:46
·
answer #3
·
answered by spanish kitty 3
·
1⤊
0⤋
If you add row 1 and row 3, then you cancel out 2 of the variables, leaving only the x so you can solve for x:
2x -y z = 4
4x y -z = 14
6x +0 +0 = 18
Solve for x:
6x = 18
x = 3
Then continue from there.
2007-01-05 17:14:34
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
x=3 y=3 z=1
I used a graphing calculator to solve it:
1) Enter the coefficients of the left side into Matrix [A] like this:
2 -1 1
1 3 -1
4 1 -1
2) Enter the numbers on the right side into Matrix [B] like this:
4
11
14
3) Solve the system by pressing [A][X^-1][B][ENTER]
2007-01-05 17:09:06
·
answer #5
·
answered by sesquipedalian 3
·
0⤊
0⤋
2x= y-z+ 4
x = (y - z + 4) / 2
3y= 11 - x + z
y= (11-x+z)/3
-z= 14 - 4x - y
z= -14+4x+y
You want to isolate each variable (x,y,z) to move things to the opposite side of the = you need to do to one side as you do to the other.
2007-01-05 17:12:40
·
answer #6
·
answered by Virginia 2
·
0⤊
0⤋
Here's how you do it:
http://fp.academic.venturacollege.edu/rbrunner/3e_3s.htm
2007-01-05 17:09:51
·
answer #7
·
answered by Jennifer L 4
·
0⤊
1⤋